The Se-Ma-For Film Studio from 1990 to 1999 - Ciszewska, Ewa (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2015)
The Se-Ma-For Film Studio from 1990 to 1999 One of the key roles in the cinematic image of Łódź (the centre of Polish film production in the 1950s and 1960s) was played by “Se-Ma-For” Film Studio. The political and economic changes that Poland underwent at the beginning of the 1990s resulted in the liquidation of most state-owned companies. Se-Ma-For studio managed to operate until 1999, when it was closed. Th is text elaborates on the circumstances that resulted in the liquidation of the studio in 1999.